Separation and mechanical properties of residual film and soil - Ren, Yu; Guo, Wensong; Wang, Xufeng; Hu, Can; Wang, Long; He, Xiaowei; Xing, Jianfei (International Journal of Agricultural and Biological Engineering, 2023)
In Xinjiang's perennial cotton (Gossypium hirsutum)-planting soil, the average residual amount of plastic film is as high as 265.3 kg/hm2, and the problem of pollution with residual plastic film in the tillage layer has become a major problem. To explore the mechanism of the separation of residual film and soil in the tillage layer and determine the conditions favorable for the separation of residual film-soil, this study established a constitutive model of residual film-soil contact based on the discrete element method and used the established constitutive model to simulate the process of separating residual film and soil. In addition, the influence of parameters, such as soil particle size and water content, on the force to separate the residual film and soil was studied using single factor and orthogonal experiments. The simulation results showed that the changing trend of the residual film-soil separation force curve did not differ much between the simulation and the actual comparison, and the curves were roughly the same. They all decreased after the separation force reached its peak value, but the simulated separation force curve was similar to that of the actual separation force. It increased rapidly from the beginning and reached peak separation force first. The single-factor experiment showed that the separation force of the used residual mulching film was higher than that of the unused mulching film. Under the same conditions, the maximum separation force required to separate the residual membrane was proportional to the positive pressure on the surface of the residual membrane and the size of soil particles. Under the same conditions, the maximum separation force required to separate the residual film is proportional to the positive pressure on the surface of the residual film and the size of soil particles. The maximum separation force decreased first and then increased as the soil moisture content increased. The results of the orthogonal experiment showed that the soil particle size had the greatest effect on the maximum separation force, followed by positive pressure on the residual film surface, soil moisture content, and the service life of mulch. In addition, film mulch that was buried 60 mm deep in the soil, a particle size of more than 2.5 mm, and a soil moisture content of 8% was the optimal combination of parameters to effectively separate the film mulching residue from the soil.Keywords: residual mulching film, soil, separation, discrete element simulation, sandy soilDOI: 10.25165/j.ijabe.20231601.7688Citation: Ren Y, Guo W S, Wang X F, Hu C, Wang L, He X W, et al. Separation and mechanical properties of residual film and soil. Int J Agric & Biol Eng, 2023; 16(1): 184–192.